2017
DOI: 10.3892/etm.2017.4928
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of microsurgery in the treatment of cerebral aneurysm rupture and its effect on NF-κB, MCP-1 and MMP-9

Abstract: The clinical efficacy of microsurgical neck clipping for the treatment of cerebral aneurysm rupture and its effect on serum nuclear factor κ-light-chain-enhancer of activated β cells (NF-κB), monocyte chemoattractant protein-1 (MCP-1) and matrix metalloproteinase-9 (MMP-9) levels were investigated. A total of 56 patients with first occurrence of cerebral aneurysm rupture were enrolled from June 2015 to June 2016. These patients were divided into control (25 patients) and observation groups (31 patients) accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…MMP-9, the main gelatinase produced by macrophages, is associated with cerebral aneurysm rupture, and may predict poor prognosis. 5,8,24 MMP-9 also plays a critical role in outward vascular remodeling in a mouse common carotid artery ligation model. 25 VNS has been shown to reduce MMP-9 expression in macrophages, 9,26 and prevent abdominal aortic aneurysm formation by suppressing inflammatory cytokines and MMP activity.…”
Section: Discussionmentioning
confidence: 99%
“…MMP-9, the main gelatinase produced by macrophages, is associated with cerebral aneurysm rupture, and may predict poor prognosis. 5,8,24 MMP-9 also plays a critical role in outward vascular remodeling in a mouse common carotid artery ligation model. 25 VNS has been shown to reduce MMP-9 expression in macrophages, 9,26 and prevent abdominal aortic aneurysm formation by suppressing inflammatory cytokines and MMP activity.…”
Section: Discussionmentioning
confidence: 99%
“…Aoki et al (2009) demonstrated that the expression of MCP-1 was up-regulated in human UIAs, which consistent with our study. In patients with ruptured IAs, the serum levels of MCP-1 were also up-regulated and could predict poor outcomes; in contrast, serum MCP-1 levels gradually decreased after these patients were treated with microsurgical clipping (Kim et al, 2008;Zhang et al, 2017). These findings suggest MCP-1 as a potential biomarker in either unruptured or ruptured intracranial aneurysms.…”
Section: Discussionmentioning
confidence: 92%
“…Multi‐planar reconstruction is a method for displaying 3D datasets and allows for the generation of cross‐sectional images, such as original two‐dimensional coronal, sagittal, and oblique images. The multi‐planar reconstruction of the curve is perpendicular to the cross‐sectional image of a particular curve made by the user (Ota, Matsukawa, & Noda, 2018; Zhang, Chen, Zheng, & Du, 2017). The 3D digital image has been upgraded to form a 3D material object.…”
Section: Discussionmentioning
confidence: 99%